EP.FRI.745 Information Sustainability: SCR+: A bespoke module to optimise information flows around the Somerset Cancer Register to enhance the multidisciplinary cancer team process. (28th October 2021) - Rahman, Fatima; Hales, Alan; Beegan, Ryan; Cable, David; Rew, David
Abstract: Background: Many surgeons work within multidisciplinary cancer teams. The Somerset Cancer Register (SCR) is a national reporting system for service performance which is in use in more than 100 NHS Trusts. However, the core system has not yet been optimised for MDT users or for the surfacing of clinical data for research and other uses. Methods: SCR replaced our legacy cancer reporting system in 2014. Working with the SCR developers, we integrated our cellular pathology and imaging records with the SCR MDT outputs. We subsequently developed SCR+ to optimise workflows for MDT coordinators and information presentation to clinical users. Results: Our HTML-enabled SCR+ software application displays all cancer patients by pathological type and year of presentation on dynamic histograms, for ease of visualisation and interaction. Every selected case is displayed in list order for each and every MDT meeting, with a fast hyperlink to our integral Lifelines EPR interface, to electronic pathology records back to 1990, and to our Breast Cancer Data System for relevant patients. Conclusions: The SCR+ module transforms the access and visualisation of cancer workload across our Trust for all authorised MDT users, with appropriate data security. The agile programming methodology allowed us to build a sustainable cancer data system with further development potential. The product substantially enhances user experience, data recall and productivity over legacy systems. Close cooperation between clinically proficient IT teams and clinicians as the end consumers of digital health data systems yields significant operational benefits at pace and with very modest costs.